Cost of Illness Pasien Hipertensi Rawat Inap di RSUP Prof. Dr. R. D. Kandou Manado - Lolo, Widya A.; Wiyono, Weny I.; Mpila, Deby A. (Universitas Sam Ratulangi, 2024)
Abstract: Besides causing systemic damage to organs, hypertensive disease also has an impact on the health economy sector (double burden disease). This study aimed to determine the cost of illness of hypertensive inpatients and its suitability with INA-CBG's tariff. This was an analytical and observational study with a cross-sectional designh. Data were collected retrospectively from the medical records of hypertensive inpatients registered as members of Jaminan kesehatan Nasional (National Health Insurance) from January to June 2024 and from financial department of Prof. Dr. R. D. Kandou Hospital Manado. Pharmaeconomic analysis was used based on hospital perspective and prevalence approach. The data were analyzed using one sample t-test to compare the congruence between cost of illness and INA-CBG’s tariff. There were 30 inpatients in this study, consisting of 10 males and 21 females. The results showed that the difference between total cost of illness and INA-CBG’s tariff was Rp.76,403,811. The one sample t-test showed that the congruence between cost of illness and INA-CBG’s tariff was significantly different based on the p-values of each code, as follows: 0.001 (I-17-14-I), 0.000 (I-17-14-II), and 0.000 (I-17-14-III). In conclusion, the total cost of illness of hypertensive inpatients at Prof. Dr. R. D. Kandou Hospital was Rp. 251,287,311 with an average per patient of Rp. 8,376,244. Moreover, overall there is a significant difference between cost of illness and INA-CBG's tariff. Keywords: cost of illness; hypertensive inpatients; Indonesian Case-based Group Abstrak: Penyakit hipertensi bukan hanya menyebabkan kerusakan sistemik di organ namun juga berdampak pada sektor ekonomi kesehatan (double burden disease). Penelitian ini bertujuan untuk mengetahui besaran terapi pasien hipertensi (cost of illness) dan kesesuaiannya dengan tarif INA-CBG’s. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Data pasien hipertensi Jaminan kesehatan Nasional (JKN) rawat inap diperoleh secara retrospektif dari Bagian Rekam Medik dan Bagian Keuangan RSUP Prof. Dr. R. D. Kandou Manado periode Januari-Juni 2024. Analisis farmakoekonomi dilakukan dengan kajian berdasarkan perspektif rumah sakit dimana kategori biaya dalam perhitungan cost of illness menggunanakan biaya medis langsung dengan pendekatan secara prevalensi. Data analisis uji beda menggunakan one sample t-test untuk mengetahui perbandingan biaya cost of illness dengan tarif INA-CBG’s. Hasil penelitian mendapatkan 30 pasien sebagai sampel, terdiri dari 10 laki-laki dan 21 perempuan. Besaran selisih antara cost of illness dengan tarif INA-CBG’s sebesar Rp. 76.403.811. Kesesuaian antara cost of illness dengan tarif INA-CBG’s menggunakan one sample t-test berbeda bermakna dengan nilai p masing-masing kode ialah 0,001 (I-17-14-I); 0,000 (I-17-14-II); dan 0,000 (I-17-14-III). Simpulan penelitian ini ialah total cost of illness pasien hipertensi rawat inap RSUP Prof Dr. R. D. Kandou sebesar Rp. 251.287.311 dengan rerata per pasien sebesar Rp. 8.376.244. Terdapat perbedaan bermakna antara cost of illness dan tarif INA-CBG’s. Kata kunci: cost of illness; pasien hipertensi; Indonesian Case-based Group